(untitled) (AmeriQuests, 2014)
The article reflects on three levels of illegality embedded in the immigration control regime in Italy: the illegality of the law, the discourse on illegal immigrants, and the non–legal space of police practices. The illegality of the regime does not emerge from one level or the other, but from the complex relationships among them: the Italian immigration law is an illegal one, and it founds its legitimacy on discourses claiming about the illegality of undocumented immigrants; police practices occur in a non-legal space, and it is the law itself that sets the boundaries of that space. Through history of the law, analyses of the discourses, and one case study I made about the interaction between undocumented immigrants and police officers in Bologna (Italy), I argue that we need focus on the links among the three levels, in order to effectively address the illegality of the regime. However, the link between police practices and legal discourses turns out to be especially very problematic, and raises the question about how to use empirical research to undermine the legitimacy of the illegal immigration control regime.